550 Workplace- and system-based interventions on return-to-work and recovery for musculoskeletal and mental health conditions: a systematic review. (24th April 2018) - Cullen, KL; Irvin, E; Collie, A; Clay, F; Gensby, U; Jennings, P; Hogg-Johnson, S; Kristman, V; Laberge, M; McKenzie, D; Newnam, S; Palagyi, A; et al.
Abstract : Introduction: The burden of managing musculoskeletal pain and injuries (MSDs) and mental health (MH) conditions in the workplace is substantial. While overall rates of work injury have declined in most high-income countries, there have not been equivalent improvements in RTW rates. The primary objective of this review was to synthesise evidence on the effectiveness of workplace- and system-based interventions for RTW and recovery after a period of work absence. Methods: We followed a systematic review process developed by the Institute for Work and Health and an adapted best evidence synthesis. Result: Seven electronic databases were searched from January 1990 until April 2015. This comprehensive search yielded 8898 non-duplicate references. Our synthesis identified 69 studies examining three types of RTW outcomes (lost time, work functioning and associated costs) and four recovery outcomes (pain, psychological functioning, physical functioning and quality-of-life). These studies examined interventions that were classified into three broad domains: healthcare provision, service delivery and workplace modifications. Our review identified that in most cases, interventions were multi-faceted and included multiple intervention components, sometimes operating across multiple domains. The most common RTW outcome reported was lost time. Among the other RTW and recovery outcomes, studies varied widely in their inclusion. There is strong evidence that interventions encompassing multiple domains are effective in improving RTW outcomes in workers with MSD or MH conditions. In contrast, there is moderate to strong evidence that most single-component interventions have no effect on improving recovery regardless of condition. Discussion: While there is substantial research literature focused on RTW, only a small percentage of these intervention studies also include measures of recovery. Identifying effective intervention programs that facilitate RTW and recovery allows workplaces to implement empirically supported programs that benefit workers through improved function and reduced pain while reducing the economic burden associated with lost time.